Monolingual and Bilingual Narrative Production and Comprehension across Cultures - Zhou, Mengqi (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2022)
Children's narrative development has been argued as more dependent on age and much less on linguistic abilities and cultural backgrounds, which is also the case for bilingual children's narrative development across two languages. Research on this topic has paid more attention to the narrative capacity of monolingual and bilingual children during the pre-school years but much less to Mandarin-speaking school-aged children and the impact of culture on their narrative development. Thus, the aim of this study is to fill this research gap, by investigating the narrative competences of monolingual Mandarin-speaking and English-Mandarin bilingual school-aged children (aged 9) in two cultural contexts, viz contemporary Irish and Chinese, with a focus on how invariant bilingual children's narrative abilities are across their two languages and how cultural and linguistic experience influences the narrative development of these groups of children. This study used a mixed research method. A total of 20 monolingual Mandarin-speaking children narrated two stories in Mandarin, and 20 English-Mandarin bilingual children narrated one story in English and one in Mandarin. The analysis was made quantitatively and descriptively by comparing the Mandarin narratives of the monolingual and bilingual groups, and the English and Mandarin narratives among the bilingual group. Data regarding children's language experiences and narrative socialisation at home and at school were collected from 40 questionnaires completed by the children's parents and eight interviews with the children's parents and teachers. The English narratives of the 9-year-old English-Mandarin bilingual children contained substantially more macrostructural components and provided more description of behaviours than their Mandarin narratives. In comparison with their monolingual peers, the bilinguals' Mandarin narratives included less concrete beginnings yet considerably more internal states as reaction, especially the emotions of the story characters. Moreover, the bilinguals fared significantly better in narrative comprehension in Mandarin than their monolingual peers, especially for the internal states of the story characters. The imbalance in language proficiency in the bilinguals' two languages, and the differences in narrative activities at home and school-based narrative instruction between the monolinguals and bilinguals may explain these findings. Additionally, the monolinguals' Mandarin narratives contained evident judgements about the moral correctness of story characters' behaviours and restrained emotional expression, which are in line with expectations about those children's narrative socialisation at home and school under the influence of Chinese culture. Overall, the present study provides rich evidence for the multiplicity of monolingual Mandarin-speaking and bilingual English-Mandarin school-aged children's narrative production. It highlights how language proficiency in bilinguals' two languages, school-based narrative instruction, and narrative activities at home and school for monolinguals and bilinguals, as well as Chinese culture, all interact and combine to influence monolingual and bilingual children's narrative skills.
APPROVED
Keywords: Narratives, Macrostructure production, Narrative comprehension, Bilingualism, Cultural Influence